Perceived Stereotyping and Seeking Care for Chronic Vulvar Pain. Issue 10 (6th June 2013) - Nguyen, Ruby H. N.; Turner, Rachael M.; Rydell, Sarah A.; MacLehose, Richard F.; Harlow, Bernard L.
Abstract Objectives We examined stereotyping of chronic pain sufferers among women aged 18–40 years and determined whether perceived stereotyping affects seeking care for women with chronic vulvar pain. Design Cross‐sectional study using a community‐based survey of vulvodynia asking if "Doctors think that people with chronic pain exaggerate their pain, " and if "People believe that vulvar pain is used as an excuse to avoid having sex". Setting and Participants Twelve thousand eight hundred thirty‐four women aged 18–40 years in metropolitan Minneapolis/St. Paul, Minnesota. Outcome Measures Women were considered to have a history of chronic vulvar pain if they reported vulvar burning lasting more than 3 months or vulvar pain on contact. Results Four thousand nine hundred eighty‐seven (38.9%) women reported a chronic pain condition; 1, 651 had chronic vulvar pain. Women experiencing chronic pain were more likely than those without to perceive stereotyping from both doctors and others; a dose–response with the number of pain conditions existed. Women with chronic vulvar pain were more likely to believe that people think vulvar pain is an excuse to avoid intercourse. Half of the women with chronic vulvar pain did not seek medical care for it; of these, 40.4% perceived stereotyping from doctors. However, it was women who actually sought care (45.1%) who were more likely to feel stigmatized by doctors (adjusted relative risk = 1.11, 95% confidence interval: 1.01–1.23). Conclusions Perceived negative stereotyping among chronic pain sufferers is common, particularly negative perceptions about physicians. In fact, chronic vulvar pain sufferers who felt stigmatized were more likely to have sought care than those who did not feel stigmatized.